2014
DOI: 10.1016/j.jmacro.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Was the European sovereign crisis self-fulfilling? Empirical evidence about the drivers of market sentiments

Abstract: International audienceWe investigate the presence of self-fulfilling dynamics during the European sovereign crisis in the light of a theoretical model that we bring to the data. Our empirical framework allows us to empirically test the presence of self-fulfilling dynamics and to identify what may have driven the market sentiment during this crisis. To do so we estimate the probability of default of five European “peripheral” countries during January 2006 to September 2011 with a panel smooth threshold regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…This result provides a new perspective on the empirical claim in Bruneau et al (2012) that the relationship between fundamental factors and the cost of debt faced by the countries of the Eurozone periphery has undergone a structural shift, and that credit derivatives have facilitated coordination on a high interest equilibrium. The simple model considered here suggests that the effect of derivatives extends beyond the coordination of expectations.…”
Section: Note Thatqmentioning
confidence: 81%
See 3 more Smart Citations
“…This result provides a new perspective on the empirical claim in Bruneau et al (2012) that the relationship between fundamental factors and the cost of debt faced by the countries of the Eurozone periphery has undergone a structural shift, and that credit derivatives have facilitated coordination on a high interest equilibrium. The simple model considered here suggests that the effect of derivatives extends beyond the coordination of expectations.…”
Section: Note Thatqmentioning
confidence: 81%
“…Furthermore, our finding that pessimistic equilibria exist for a broader range of funding requirements in the presence of unrestricted credit derivatives than in their absence also suggests that firms with traded credit derivatives could experience particularly adverse shifts in the terms of financing under stressed market conditions. Bruneau et al (2012) have recently argued that an abrupt and self-fulfilling change in expectations of default was a key factor in accounting for the sharp rise in interest rates paid by the countries of the eurozone periphery. They argue that the relationship between fundamentals and credit spreads was subject to a structural break around March 2010, indicative of a switch to a different equilibrium with greater pessimism about default.…”
Section: Empirical Evidence and Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, empirical literature documented the importance of self-fulfilling factors for explaining the Eurozone sovereign debt crisis (De Grauwe and Ji (2013), Bruneau et al (2014), and Schumacher (2014)). These papers -relying on empirical applications to sovereign debt crises of the theoretical literature on second-generation speculative attack models (Obstfeld, 1996) -showed that peripheral Eurozone economies with relatively good fiscal fundamentals faced strong increases in sovereign bonds spreads, due to episodes of exogenous distrust in international financial markets.…”
mentioning
confidence: 99%